Meningkatkan Kinerja Guru Kelas dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Melalui Supervisi Klinis di SDN 03 Pakan Kurai Kecamatan Guguk Panjang Kota Bukittinggi - Misyar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Developing a learning implementation plan is one of the skills of a professional teacher as statedin Permendikbud No. 20 of 2016. Most of the teachers observed in the study were still not able to prepare lesson plans properly. The purpose of this study was to see the effect of clinical supervision on improving the performance of classroom teachers in making lesson plans (RPP).This research is School Action Research (PTS). The research subjects consisted of class teachersat SDN 03 Pakan Kurai, Guguk Panjang District, Bukittinggi City. The results showed thatclinical supervision could improve teacher performance in preparing the Lesson Plan (RPP) at SDN 03 Pakan Kurai, Guguk Panjang District, Bukittinggi.